Pengembangan Kinerja Karyawan Efek Dari Kepemimpinan dan Budaya Organisasi dalam Organisasi Binar Academy - Josiah Arifin Pardamean; Meidy Lieke Karundeng (Departement of Mathematics Education, 2023)
This research has a purpose in proving what result will be given by the leadership and organization culture to the worker’s performance. Using the people who works at Binar Academy Organization as the population of this research. Using questionnaire as the technique in collecting the data with the total of 60 people, and analyzing the data using SEM-PLS software with the inner and outer model. The result showed that there are significant relationships between :1. Leadership and worker’s performance, 2. Organization culture and worker’s performance, 3. Leadership and worker’s performance. And there is no significant relationship between leadership and organization culture.